Evaluation of Developmental Toxicity and Oxidative Stress Caused by Zinc Oxide Nanoparticles in Zebra Fish Embryos/ Larvae - Deenathayalan, Uvarajan; Nandita, Ravichandran; Kavithaa, Krishnamoorthy; Kavitha, Vengamuthu Subramaniyan; Govindasamy, Chandramohan; Al-Numair, Khalid S.; Alsaif, Mohammed A.; Cheon, Yong Pil; Arul, Narayanasamy; Brindha, Durairaj (Applied biochemistry and biotechnology, 2024)
Zinc oxide nanoparticles (ZnO NPs) are used in various fields, including biological ones. ZnO NPs are eventually disposed of in the environment where they may affect natural systems, and there is no international law to regulate their manufacture, usage, and disposal. Hence, this present study is carried out to synthesise a more non-toxic and bioactive ZnO NPs from the marine algae Sargassum polycystum . The ZnO NPs were biologically produced using the marine algae Sargassum polycystum . The dynamic light scattering result describes that synthesised particles’ average size is about 100 nm in diameter. Transmission electron microscopy (TEM) analysis demonstrated the rod-like morphology of ZnO NPs. Fourier tranform-infrared spectroscopy (FT-IR) results revealed the presence of functional groups in ZnO NPs. The selected area electron diffraction (SAED) results strongly suggested the ZnO NPs crystallinity. ZnO NPs surface morphology and compositions were identified by scanning electron microscopy (SEM- EDX) values. To analyse the toxicity of synthesised nanoparticles, zebra fish larvae were used, which involved subjecting embryos to various ZnO NPs concentrations at 1 hpf and analysing the results at 96 hpf. The 60 and 80 ppm sub-lethal doses were chosen for further studies based on the LC 50 (82.23 ppm). In the ZnO NPs-treated groups, a significant slowdown in pulse rate and a delay in hatching were seen, both of which impacted the embryonic processes. A teratogenic study revealed a dose-dependent increase in the incidence of developmental deformities in the treated groups. Along with increased oxidants and a corresponding reduction in antioxidant enzymes, Na + K +− ATPase and AChE activity changes were seen in ZnO NPs-treated zebra fish larvae groups. The apoptosis process was increased in ZnO NPs-treated groups revealed by acridine orange staining. These results indicate that the green synthesis process cannot mitigate the oxidative stress induced by ZnO NPs on oxidative signalling.